Pengembangan E-Learning untuk Bimbingan Teknis Lembaga Penjaminan Mutu Pendidikan - Prasetyo, Edi; Rusijono, Rusijono; Mariono, Andi (JOEAI (Journal of Education and Instruction), 2021)
This study aims to produce appropriate and effective E-learning to be used in the implementation of technical guidance learning at LPMP East Java. The research carried out is included in the research and development model using the ADDIE method. Data collection techniques were carried out using questionnaires and test instruments. The feasibility of the media is assessed from the data obtained from material experts, media experts, media learning experts, facilitators to targets. The effectiveness of the product is assessed from the test results during field trials to the target. Based on the results of the research conducted, the results showed that: (1) in general the feasibility test from 3 experts showed that the product developed was very feasible to use; (2) The developed e-learning has a good effectiveness in increasing the participants' understanding which is assessed based on the test results. It can be concluded that E-learning is very useful to be developed in learning media, and the effectiveness of the use of E-learning has a positive impact on increasing the understanding of the material for technical guidance participants. The conclusion is that E-learning is very useful to be developed in learning media, and the effectiveness of the use of E-learning has a positive impact on improving the understanding of the material for technical guidance participants. Keywords: Technical Guidance, E-learning, Development